How Do Consumers See Firms' Family Nature? A Review of the Literature. (March 2020) - Andreini, Daniela; Bettinelli, Cristina; Pedeliento, Giuseppe; Apa, Roberta
This literature review analyzes studies that deal with the meanings that consumers form about firms' family nature. Through the analysis of 83 papers, we highlight the importance of firms' family nature from consumers' perceptual, social, and cultural perspectives, at the micro, meso, and macro levels. Beside the common meanings that consumers attach to firms' family nature, our review showed that in some cases, firms' family nature acquired meanings that were deemed to be so important that they eventually provided consumers with self-identification, communitarian identification, and novel market configurations, and even made the family firm the industry's prototypical organizational form.